Bioequivalence and Pharmacokinetics Comparison of Two Formulations of Extended-Release Pentoxifylline Tablets in Healthy Subjects after Fasting and Fed Conditions - Jaafar J. Ibraheem Al-Tamimi (College of Pharmacy University of Baghdad, 2017)
The pharmacokinetics and bioequivalence of a newly developed extended-released (ER) tablet containing 400 mg pentoxifylline as a test product was compared with the reference brand product TrentalÂ® 400 mg ER tablet produced by Sanofi-Aventis. Two separate studies were conducted simultaneously. The first study was conducted under fasting condition, whereas, the second study was conducted under fed condition; using the same batches of the test and reference products in both studies. In each study, both products were administered to 32 healthy male adult volunteers applying a single-dose, two-treatment, two-period, two-sequence, randomized crossover design with one-week washout period between dosing. Twenty two blood samples were withdrawn from each volunteer over 24 hours period.  Pentoxifylline concentrations were determined in plasma by a validated HPLC method according to FDA Bioanalytical Method Validation Guidance using UV detection and chloramphenicol as internal standard. The lower limit of quantitation of the drug in plasma was 5 ng/ml and the upper limit of quantitation was 500 ng/ml. From the plasma concentration-time data of each individual, the pharmacokinetic parameters; Cmax,  AUC0-t, AUC0-Â¥, Cmax/AUC0-Â¥, Tmax, lZ & T0.5; were calculated applying non-compartmental analysis. Data of the test and reference products were statistically analyzed to test for bioequivalence of the two products, using criteria of FDA and EMEA Guidance.  The pharmacokinetic parameters mentioned above were statistically analyzed by descriptive statistics, ANOVA test and 90% Confidence Interval (CI). ANOVA test involved the calculation of the effects of: treatment, period, sequence and subjects nested in sequence. According to the above guidance, the primary pharmacokinetic parameters used for bioequivalence testing, namely Cmax, AUC0-t and AUC0-Â¥ were also statistically analyzed by ANOVA & CI tests using the corresponding Ln-transformed values. The mean values  Cmax,  AUC0-t , AUC0-Â¥ , Cmax/AUC0-Â¥ , Tmax, lZ & T0.5 for the test formula obtained from the fasting study  were; 144.4 ng/ml,  845.4 ng.hr/ml, 868.4 ng.hr/ml, 0.186 hr-1, 3.29 hr, 0.561 hr-1 and 1.65 hr, respectively; and the mean values of these parameters for the reference formula were; 150.0 ng/ml,  871.1 ng.hr/ml, 893.7 ng.hr/ml, 0.177 hr-1, 3.70 hr, 0.558 hr-1 and 1.59 hr,  respectively.  The mean values of the above mentioned parameters for the test formula obtained from the fed study were; 157.8 ng/ml, 826.5 ng.hr/ml, 853.8 ng.hr/ml, 0.198 hr-1, 5.4 hr, 0.458 hr-1 and 2.06 hr, respectively; and the mean values of these parameters for the reference formula were; 162.1 ng/ml, 869.7 ng.hr/ml, 894.8 ng.hr/ml, 0.196 hr-1, 4.1 hr, 0.525 hr-1 and 1.80 hr, respectively.  Based on criteria of FDA and   EMEA Guidance on Bioavailability and Bioequivalence, the results of the fasting and fed studies demonstrated bioequivalence of the two products under either condition. Accordingly, it is concluded that the newly developed ER tablet containing 400 mg pentoxifylline is bioequivalent to TrentalÂ® 400 mg ER tablet produced by Sanofi-Aventis. Keywords: Pentoxifylline, Pharmacokinetics, Bioequivalence.